Transcultural Diabetes Nutrition Algorithm: Brazilian Application - Moura, Fabio (Nutrients, 2015)
The prevalence of obesity, pre-diabetes, and type 2 diabetes (T2D) is increasing worldwide, especially in the developing nations of South America. Brazil has experienced an exponential increase in the prevalence of these chronic non-communicable diseases. The rising prevalence is probably due to changing eating patterns, sedentary living, and a progressive aging of the population. These trends and their underlying causes carry untoward consequences for all Brazilians and the future of Brazilian public health and the healthcare system. Lifestyle changes that include healthy eating (nutrition therapy) and regular physical activity (structured exercise) represent efficient inexpensive measures to prevent and/or treat the aforementioned disorders and are recommended for all afflicted patients. Regrettably, the implementation of lifestyle changes is fraught with clinical and personal challenges in real life. The transcultural Diabetes Nutrition Algorithm (tDNA) is a therapeutic tool intended to foster implementation of lifestyle recommendations and to improve disease-related outcomes in common clinical settings. It is evidence-based and amenable to cultural adaptation. The Brazilian Diabetes Association, Society of Cardiology and Ministry of Health guidelines for nutrition therapy and physical exercise were considered for the Brazilian adaptation. The resultant tDNA-Brazil and its underlying recommendations are presented and explained.